1987
DOI: 10.1111/j.1651-2227.1987.tb17122.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Linear Growth Using a Mathematical Model. II. From 3 to 21 Years of Age

Abstract: Analysis of linear growth using a mathematical model. 11. From 3 to 21 years of age. Acta Paediatr Scand [Suppl] 337:12, 1987.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
0
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 12 publications
4
80
0
2
Order By: Relevance
“…It has been shown that girls who mature early tend to be tall for their age a t onset of menarche, but the longer growth period of later maturers, may explain why they often become taller as adults than the early maturer (26,27). Naturally, caloric restriction during childhood is likely to modify this pattern, resulting both in later age at menarche and lower adult height.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that girls who mature early tend to be tall for their age a t onset of menarche, but the longer growth period of later maturers, may explain why they often become taller as adults than the early maturer (26,27). Naturally, caloric restriction during childhood is likely to modify this pattern, resulting both in later age at menarche and lower adult height.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, height SDS for prepubertal children had to be obtained from the childhood part in the Swedish reference. The childhood reference gives an accurate estimate of height, as it does not underestimate height if puberty is delayed (22). Achieved FH was defined as the time point 1 y after height velocity Ͻ1 cm/y.…”
Section: Methodsmentioning
confidence: 99%
“…All children were classified as prepubertal, according to Tanner & Whitehouse (29) regarding breast and pubic hair development, and according to Zachmann et al (30) regarding testicular volume as measured by an orchidometer. Height, weight and weight for height (W/H) at the time of the study were expressed as standard deviation scores (SD score) compared with Swedish reference values (31)(32)(33). All the children were healthy and did not deviate on weight charts nor had they anamnesis or signs of undernutrition.…”
Section: Subjectsmentioning
confidence: 99%